CHATBOT IMPLEMENTATION TO SUPPORT MOBILE LEARNING DURING NCOVID19 PANDEMIC - Putri Sakinah; Yaya Heryadi (Jurnal Ipteks Terapan, 2020)
This paper presents the results of chatbot implementation to support mobile learning in higher education. Thegoal of the chatbot implementation in this study, among others, is to address high interest of higher educationin Indonesia toward online learning support mainly during the resent NCOVID19 pandemic in which most oflearning process are implemented using online learning mode. The proposed chatbot prototype has been testedin the University of Andalas, Sumatera, Indonesia. The chatbot is designed using standard softwareengineering method and implemented using Android-based mobile application flatform. Respondents for thechatbot evaluation are chosen based on purposive random sampling among students of Department ofSociology as sampling population. The data collecting is implemented using survey method with selfadministered questionnaires. The overall evaluation results showed that the designed and implementation hasmet the students’ expectation. Interestingly most of the respondents showed their interest to use the chatbot